Identification of previously untypable RD cell line isolates and detection of EV-A71 genotype C1 in a child with AFP in Nigeria (2018)
We previously attempted to identify 96 nonpolio enteroviruses (EVs) recovered in RD cell culture from children <15years with acute flaccid paralysis in Nigeria. We succeeded in identifying 69 of the isolates. Here, we describe an attempt to identify the remaining 27 isolates. Twenty-six (the 27th isolate was exhausted) isolates/samples that could not be typed previously were further analyzed. All were subjected to RNA extraction, cDNA synthesis, enterovirus 5ʹ-UTR–VP2 PCR assay and a modified VP1 snPCR assay. Both the 5ʹ-UTR–VP2 and VP1 amplicons were sequenced, isolates identified and subjected to phylogenetic analysis. Twenty of the 26 samples analyzed were identified. Altogether, 23 (three samples had co-infection) EV strains were recovered. These belong to 11 EV (one EVA, nine EVB and one EVC) types which were EVA71 genotype C1 (1 strain), CVB3 (7 strains), CVB5 (1 strain), E5 (2 strain), E11 (3 strains), E13 (2 strain), E19 (1 strain), E20 (1 strain), E24 (2 strains), EVB75 (1strain) and EVC99 (2 strains). Of the 11 EV types, the 5ʹ-UTR-VP2 assay identified seven while the VP1 assay identified 10. Both assays simultaneously detected 7 of the 11 EV types identified in this study with 100% congruence. We successfully identified 20 of 26 samples that were previously untypable. We also provided evidence that suggests a clade of EVA71 genotype C1 might have been circulating in sub-Saharan Africa since 2008. Finally, we showed that the 5ʹ-UTR -VP2 assay might be as valuable as the VP1 assay in EV identification.